A lost generation? Kony, conflict, and the cultural impacts in northern Uganda - Westfall, David W. (Kansas State University, 2017)
For over two decades the people of northern Uganda endured horrific atrocities during Africa’s forgotten war in the form of attacks and child abductions by the Lord’s Resistance Army, animal rustling by neighboring ethnic groups, and internal displacement of an unimaginable 90 percent of the northern parts of the country. With the majority of internally displaced persons spending over a decade in IDP camps, an entire generation of Acholi was socialized and acculturated in a non-traditional environment. A decade after the last LRA attack, I ask, what are the cultural impacts of the conflict and how has the culture recovered from the trauma. Using ethnographic analysis, this dissertation is rooted in over 150 interviews. While it has been presented to the world at large that Joseph Kony’s LRA is the one of the biggest problems facing the region, I found it is not the case. Interviewees discussed serious inadequacies in education, land conflict, culture loss, climate change, drought, famine, a perceived generational divide, and a strong distrust of the Ugandan government. Additionally this research examines the case of Uganda through the lens of, and attempts to build upon, Jeffrey Alexander’s cultural trauma process. I argue the increasing reach and instantaneous nature of social media can interact with, alter, and prolong the trauma process. The externalization of defining a problem and solutions for that problem while the trauma process is occurring, or shortly after the trauma has subsided, can lead to retraumatization.
Keywords: Uganda; Lord's Resistance Army